Smart key using keypad / Nor Afidah Abdullah and Siti Mariam Jusoh - Abdullah, Nor Afidah; Jusoh, Siti Mariam (2005)
Final project is the part of the course structure that needs to be taken by student that is in the final years. This project has been divided into two that is called Project 1 (K.EU 280) and Project 2 (KEU 380). The main purpose that students have to take this course is to give them opportunity to test their skills and to gather all the knowledge that they have been studying for these few years. From this kind of course, we can learn the practical way of doing the project and figure out the best way to improve them for the purpose of using them in the future. Nowadays, the rapid changes in quality of life require new technologies to fix with them. It is important to design new system that can make everything as simpler as possible to operate. That why we choose the project base on keypad. This equipment has been invented and is now has been use in life and become the important thing to people. We realized that this course is to train the students to be familiar with making a certain project. A smart door using keypad is designed circuits that been created to make life easy in everyday life. From that, we design the circuit that can open and lock the door with only pressing a few codes. This circuit is connected the ‘Programmable Digital Coded Lock’ to the magnetic switch. Actually this circuit is normally closed. With pressing three secret code, the door will be open. The proposed of this project is to open the door using ‘Programmable Digital Coded Lock’ and the magnetic switch will free the latch when the pin code is pressing. In this report, a detailed description of the components used to implement the circuit together with the explanation of how the circuit is operating.